Fatigue in patients with Behçet's syndrome: relationship with quality of life, depression, anxiety, disability and disease activity. (23rd February 2016) - Ilhan, Birkan; Can, Meryem; Alibaz‐Oner, Fatma; Yilmaz‐Oner, Sibel; Polat‐Korkmaz, Ozge; Ozen, Gulsen; Mumcu, Gonca; Maradit Kremers, Hilal; Direskeneli, Haner
Abstract: Objectives: Fatigue is a common symptom of chronic inflammatory diseases. The objective of this study was to investigate fatigue in patients with Behçet's syndrome (BS) and to examine the relationship between fatigue and disease activity, quality of life, anxiety and depression. Methods: This is a cross‐sectional study of 123 BS patients and 71 healthy controls in Turkey. All subjects completed the Multidimensional Assessment of Fatigue (MAF) questionnaire, Short form‐36 (SF‐36), Hospital Anxiety and Depression (HADS) scale and Health Assessment Questionnaire (HAQ). Disease activity among BS patients was assessed using the Behçet Syndrome Activity Scale (BSAS) and the physician's global assessment (PGA). Results: BS patients had significantly higher MAF, HADS‐depression (HADS‐D) and HADS‐anxiety (HADS‐A) scores than the healthy controls ( P  <   0.001). Both the physical and mental components of the SF‐36 scale were impaired in BS patients ( P  =   0.0001). BS patients with active disease, depression and anxiety had significantly higher MAF scores compared to BS patients without active disease, depression and anxiety ( P  =   0.0001). MAF scores showed positive correlations with HADS‐A, HADS‐D, HAQ scores and negative correlations with SF‐36 mental and physical components. In regression analyses, depression, anxiety and physical dysfunction were significantly associated with fatigue, after adjusting for age, sex, SF‐ 36 physical and mental scores, HAQ, HADS‐A, HADS‐D and BSAS scores ( P  <   0.05). Decreases in SF‐36 physical and mental scores were significant predictive factors for high MAF score in healthy controls ( P  <   0.05). Conclusions: Fatigue is common in clinically active BS patients compared with healthy controls and inactive BS patients. Depression, anxiety and physical dysfunction were significantly associated with fatigue.